Distribution of dew and its importance in moisture balance for rabi crops in India (MAUSAM, 1990)
. In this study an attempt has been made to determine' geographical distribution of the dewfall. The study utilises 18 years data (1971-88) for a fairly well distributed network of stations, Vertical profile of the dew, deposits have been fitted. To a heretical distribution. Contribution of dew to the monthly precipitation and the extent to which dewfalls able to meet the evaporative demands of the crops have been examined. Time taken for the dew to evaporate after sunrise has also been discussed.